Making Collage Work in Learning of Elementary School: A Study Of Student Creativity - Julfatu Jahra (Papanda Publisher, 2022)
Creativity is an important aspect that elementary school students need to have. However, several studies show that students' creativity is still low. One of the learning activities that are thought to be able to develop children's creativity is by making collage works. In the activity of making collages, children can be creative according to their own creativity. This study aims to increase students' creativity by using collage techniques. This research method uses classroom action research with the Kemmis and McTaggart design carried out in four stages, namely planning, implementation, observation and reflection. The subject of this research is the fourth-grade students of SDN Ciseureuh for the academic year 2021/2022, with a total of 14 participants, consisting of 3 boys and 11 girls. Data collection techniques in this study are using observation and interview techniques. The results showed that the creativity of students in the pre-cycle obtained an average score of 50.45 the category began to develop, in the first cycle it increased to 74.11 the category developed as expected, and in the second cycle it increased to 87.50 the category developed very well. From these results, the conclusion of this study is that the college method can increase the creativity of fourth-grade students at SDN Ciseureuh.